Multibody Mechatronic Systems Proceedings of the MUSME Conference held in Florianópolis, Brazil, October 24-28, 2017 - Carvalho, João Carlos Mendes; Martins, Daniel; Simoni, Roberto; Simas, Henrique (Mechanisms and Machine Science,, 2018)
These are the Proceedings of the 6th International Symposium on Multibody Systems and Mechatronics (MUSME 2017) which was held in Florianópolis, Brazil, October 24-28, 2017.  Topics addressed include analysis and synthesis of mechanisms; dynamics of multibody systems; design algorithms for mechatronic systems; simulation procedures and results; prototypes and their performance; robots and micromachines; experimental validations; theory of mechatronic simulation; mechatronic systems; and control of mechatronic systems. The MUSME 2017 Symposium was one of the activities of the FEIbIM Commission for Mechatronics and IFToMM technical Committees for Multibody Dynamics, Robotics and Mechatronics.